Production and Biomass of Pokea Clam (Batissa violacea var. celebensis von Martens, 1897) in the Langkumbe River Waters North Buton Southeast Sulawesi - Tri Abdul Rahman; Bahtiar Bahtiar; Pramono Hery Santoso (Masyarakat Moluska Indonesia, 2021)
Langkumbe River is located in West Kulisusu District and has long been used by the community for various daily activities. One of the resources often used by the people around Langkumbe River is pokea clams. The aim of this study was to determine the production and biomass of pokea clams (B. violacea) in Langkumbe River Waters of North Buton Regency from August to October 2017. The sampling method used was swept area method using a traditional fishing gear